Prognostic Factors for Cancer-Specific Survival and Disease-Free Interval in 130 Patients with Follicular Thyroid Carcinoma: Single Institution Experience - Matija Buzejic; Zoran Bukumiric; Branislav Rovcanin; Milan Jovanovic; Marina Stojanovic; Goran Zoric; Katarina Tausanovic; Nikola Slijepcevic; Vladan Zivaljevic (Diagnostics)
Background: Follicular thyroid carcinoma (FTC) is categorized into three groups: minimally invasive FTC (MIFTC), encapsulated angioinvasive FTC (EAIFTC), and widely invasive FTC (WIFTC). FTC is the second most common type of thyroid tumor, though it remains relatively rare in the general population. This study aimed to examine the prognosis and prognostic factors in patients with follicular thyroid carcinoma. Methods: Data were obtained from a tertiary referral center for 130 FTC patients, covering the period from 1995 to 2020. Clinical data included demographic characteristics, tumor features, type of surgery, tumor recurrence, and vital status. Descriptive statistical methods, Kaplan–Meier survival curves, and Cox proportional hazard regression were used for statistical analysis to identify independent predictors. Results: Distant metastases occurred in 12 patients during the follow-up period. The 5-year, 10-year, 15-year, and 20-year cancer-specific survival (CSS) rates were 98.1%, 92.3%, 83.5%, and 79.8%, respectively. Independent unfavorable prognostic factors for CSS included widely invasive tumor type (hazard ratio [HR] 3.63, 95% CI 1.29–10.18), multifocality (HR 6.7, 95% CI 1.37–32.72), and presence of distant metastases (HR 2.29, 95% CI 1.08–4.84). When disease-free interval (DFI) was considered, the 5-year, 10-year, 15-year, and 20-year rates were 92.3%, 85.3%, 82.0%, and 76.6%, respectively. Independent unfavorable prognostic factors for DFI were widely invasive tumor type (HR 2.53, 95% CI 1.02–6.28) and tumor multifocality (HR 7.69, 95% CI 1.07–55.17). Conclusions: The 10-year survival rate for patients with FTC is relatively favorable. Factors associated with poorer prognosis include the presence of distant metastases, WIFTC, and multifocality. Factors linked to disease recurrence are WIFTC and multifocality.